Religious tolerance is an important factor in ensuring political stability - Akmal Akhmedovich Akhmedov; Laylo Sadrievna Azizova (International Journal on Orange Technologies, 2020)
This article analyzes the genesis, stages of development, content and essence of religious tolerance, and its place and role in our social development in a philosophical context.